EDUKASI PIJAT BAYI UNTUK PENCEGAHAN STUNTING DAN OPTIMALISASI TUMBUH KEMBANG ANAK - Oktaviani, Ika; Ajeng, Atnesia (Universitas Muhammadiyah Tangerang, 2023)
Stunting is a problem that is often encountered in infants and toddlers and can result in increased morbidity and mortality. Prevention and management of stunting can be done with complementary therapy with baby massage to stimulate growth and development. Providing baby massage treatment is the best and cheapest form of alternative treatment in an effort to increase the baby's weight optimally so as to increase the baby's weight and increase the child's growth and development in the future. Method: There were 15 participants. This activity was carried out for 60 minutes of counseling and 60 minutes of teaching baby massage to the mother. In this activity, the participants are babies and toddlers as well as their respective mothers or companions in the RW 08 Periuk Damai Housing Complex, Tangerang-Banten City, Posyandu Melati VIII and want to know information about Baby Massage Education for Stunting Prevention and Optimizing Child Growth and Development.. This activity was held on Agustus,24 2023. During the socialization, the participants actively asked the instructor about the material presented. All participants looked enthusiastic about participating in the activity and actively in the discussion. The results of the pre-test and post-test shows that the frequency distribution of pre-test baby massage education with good knowledge was 4 respondents (27%), 11 respondents (73%) had poor knowledge. Frequency distribution of post-test baby massage education with good knowledge was 13 respondents (87%), with poor knowledge was 2 respondents (13%). Growth and development examination with KMS was good for 5 respondents (33%) or less for 10 respondents (67%)%. There needs education about massage for child to increase growth and development also to prevent stunting.